Exploring "Intersubjectivity Negotiation Episodes" and "Language Related Episodes" in Second‐Language Peer Interaction. Issue 1 (18th April 2022) - Toth, Paul D.; Gil‐Berrio, Yohana
Abstract: This study examines learner deliberations over their discursive plans during second language (L2) instructional tasks, which we call intersubjectivity negotiation episodes (INEs). We argue that these provide essential contexts for negotiations over L2 form‐meaning mappings, known as language related episodes (LREs). Our data comes from two intact third‐year Spanish classes at a U.S. public high school, where four groups of 19 total learners completed four communicative tasks over three 90‐minute lessons. We found that learners spent more time in INEs than LREs overall, and in most task performances. We identified four INE functions: deliberations over discursive goals and means, progress toward task completion, and the interpretive framing of contributions. Among these, tasks with greater potentially relevant content yielded more means and progress INEs, while those requiring content from personal experience yielded more framing INEs. Individual agency and group composition also affected the amount of INEs. Theoretical and pedagogical implications are discussed. Abstract :